PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V.C SD NEGERI 62 PEKANBARU - Mantili, Dewi; Alim, Jesi Alexander; Syahrilfuddin, Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstarck : This research was aimed to increase learning proces and student achievement of science lesson V.C grade years of 2014 / 2015. Subject of this research is student V.C grade of state elementary school 62 Pekanbaru which is total 35 students, consisted of 12 girls and 16 boys. This was a classroom research which has two cycles.the data shown either learning proces icreased. The basic score of daily examination as 9,75 which 16 students passed and 14 students failed. The ending of daily examination was as 53,33%. The second daily examination alsos increased from basic score as 31,30% which 27 students passed and 3 students failed. The ending of second daily examination was 90%. Based on the expalanation above it can be concluded that the imlpementation learning cooperatif type numbered heads together (NHT) increased students’ achievement in science lesson of students V.C grade of state elementary school 62 Pekanbaru.Keywords : Cooperatf Numbered Heads Together (NHT), Student Achievement the result Of Science Studies.